The effects of Gamma radiation on a PBX containing TATB and the fluoropolymer FK-800 - Connors, S. C. (Cranfield University, 2014)
The polymer bonded explosive TCV is analogous to PBX compositions used in some nuclear weapons where the PBX will be exposed to high energy ionising gamma radiation. It is therefore important to study how gamma radiation affects the mechanical and chemical properties of the PBX. In this study 60Co was used to irradiate samples of the TCV, its FK-800 binder and TATB explosive filler, at 37.5 °C, to total doses up to 200 kGy in air and under vacuum. Post irradiation analysis consisted of mechanical, thermal and chemical analysis of the irradiated materials. Results from the radiolysis of the FK-800 showed predominant main chain scission taking place, these results in the release of volatile fluorine containing products and an increase in the polymer’s crystallinity. The changes to the FK-800’s structural properties result in an increase in Young’s modulus and yield stress whilst reducing both ultimate tensile strength and elongation at maximum stress. Dynamic mechanical analysis shows the material softening initially upon irradiation, then stiffening as crystallinity increased. TATB was found to turn green and have increased sensitiveness to impact and electric spark discharge with gamma radiation. Analysis by HPLC and LC-MS identified a decomposition product with a mass of 240 g mol-1. No significant changes to the mechanical properties of TCV were identified; however, its sensitiveness to impact and electric spark discharge were found to increase similar to TATB’s. In conclusion, gamma irradiation of TCV has identified significant changes to the mechanical and chemical properties of the FK-800 binder, have little to no effect on mechanical properties of PBX up to 100 kGy. The predominant radiolytic effects on TCV were to its hazard characteristics caused by changes in the TATB. A mono-furazan derivative of TATB has been suggested as the decomposition product identified, and as a possible cause for the increase in sensitiveness of TATB upon gamma irradiation.